Advancing digital patient-centered measurement methods for team-based care. (December 2022) - Antonio, Marcy G; Davis, Selena; Smith, Mindy; Burgener, Paul; Price, Morgan; Lavallee, Danielle C; Fletcher, Sarah; Lau, Francis
Objectives: To conceptualize new methods for integrating patient-centered measurement into team-based care. Methods: A standalone portal was introduced into a rural clinic to support conceptualization of new methods for integration of patient-centered measurement in team-based care. The portal housed mental health-related online resources, three patient-reported measures and a self-action plan. Six providers and four patients used the portal for four months. Our data collection techniques included clinic discussions, one-on-one interviews, workflow diagrams and data generated through the portal. Analysis was supported through coding interview transcripts, looking across multiple sources of research data and research team discussions. Results: Our research team conceptualized five team-based patient-centered measurement methods through this study. Patient-centered measurement Team Mapping offfers a technique to provide greater clarity of care-team roles and responsibilities in data collected through patient-centered measurement. Longitudinal Care Alignment can guide the care-team on incorporating patient-centered measurement into ongoing provider–patient interactions. Digital Tool Exploration can be used to evaluate a team's readiness toward digital tool adoption, and the impact of these tools. Team-based quality improvement serves as a framework for engaging teams in patient-centered quality improvement. Shared learning is a method that promotes patientprovider interactions that validate patient's perspectives of their care. Conclusion: The portal illuminated new methods for the integration of patient-centered measurement in team-based care. The first three proposed patient-centered measurement methods provides ways to assess how a clinic can incorporate patient-centered measurement methods into team-based care. The latter two methods focus on the aim of patient-generated data in which patient's values and perspectives are represented and quality of patient-centered care can be evaluated. Further testing is needed to assess the utility of these patient-centered measurement methods across different clinical settings and domains.